2019
DOI: 10.1021/acs.organomet.9b00254
|View full text |Cite
|
Sign up to set email alerts
|

Tunable SiN Hybrid Conjugated Materials

Abstract: We report the synthesis of a family of N-aryl cyclosilazanes. The reaction of 1,2-bis­(trifluoro­methanesulfonate)­tetramethyl­disilane with para-substituted anilines gives six-membered rings with no observed condensation polymerization. X-ray crystallography reveals the cyclosilazane adopts a twist boat conformation with both nitrogens in a trigonal planar geometry. Solution phase UV–vis spectroscopic studies coupled with density functional theory calculations interrogate the ability of the nitrogen atom to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Thiophenol, 4-bromothiophenol, p-thiocresol, and benzene-d 6 were all purchased from commercial sources. 1 H NMR, 13 C { 1 H} NMR, and 29 Si { 1 H} NMR spectra were recorded on either a Bruker Advance 300, 400, or III HD 400 MHz spectrometer, and chemical shifts are reported in parts per million (ppm). Spectra were recorded in benzene-d 6 or chloroform-d 1 with the residual solvent peak as the internal standard ( 1 H NMR: C 6 H 6 δ = 7.16, CHCl 3 δ = 7.26; 13 C NMR: C 6 H 6 δ 128.06, CHCl 3 δ = 77.16).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiophenol, 4-bromothiophenol, p-thiocresol, and benzene-d 6 were all purchased from commercial sources. 1 H NMR, 13 C { 1 H} NMR, and 29 Si { 1 H} NMR spectra were recorded on either a Bruker Advance 300, 400, or III HD 400 MHz spectrometer, and chemical shifts are reported in parts per million (ppm). Spectra were recorded in benzene-d 6 or chloroform-d 1 with the residual solvent peak as the internal standard ( 1 H NMR: C 6 H 6 δ = 7.16, CHCl 3 δ = 7.26; 13 C NMR: C 6 H 6 δ 128.06, CHCl 3 δ = 77.16).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Since the discovery in the 1960s that permethylcyclosilanes exhibit longer-wavelength absorption spectra than cycloalkanes and form stable radical anions, interest in the synthesis of increasingly complex cyclosilanes has only grown . Prismatic solids , and polycyclic silanes have shed light on the impact of strain and curvature on σ-conjugation, while we have investigated the synthesis of stereochemically defined cyclosilanes. An interest in the influence of heteroatomic substitution on optoelectronic properties has inspired work on boron- and nitrogen-containing cyclosilanes. , Herein, we report the synthesis of cyclosilane thioethers via chemoselective dehydrocoupling of partially hydrogenated cyclosilanes and arylthiols and examine the effect of structural isomerism on conjugation. Density functional theory (DFT) calculations were used to elucidate potential mechanisms underlying experimental observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that permethylated oligosilanes can be induced with light to donate electrons to the electron acceptor tetracyanoethylene (TCNE), suggesting that σ–π conjugated hybrid materials might be expected to exhibit photoinduced intramolecular charge-transfer. These discoveries prompted the design of new organosilane materials with silane-bridged donor–acceptor units as a common architecture and the interrogation of their photoinduced charge-transfer and nonlinear optical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Towards the goal of uncovering new nanostructured materials that combine these compelling properties with the processability and tunability of organic conjugated polymers, we reported the synthesis of organosilicon polymer mimics of the crystalline silicon lattice such as polycyclosilane poly(1,4Si 6 ) (Scheme 1a). [16] Key to this work is the synthesis of multifunctional cyclosilanes [17,18] amenable to dehydrocoupling [19][20][21][22][23] or reductive polymerization. [24] The rational design and synthesis of new building blocks could further expand the structural and functional diversity of polycyclosilanes and other nanostructured silanes.…”
mentioning
confidence: 99%